Предмет: Математика,
автор: ega1999
Помогите пожалуйста.Очень нужно.Буду Благодарен.
Приложения:
Ответы
Автор ответа:
0
1)y⁾=tgx⇒y⁾=-3x²; x₀=-1; tgx=y⁾(-1)=-3
2)y=x²-5x; y⁾=2x-5
3) a)y⁾=(2-cosx)(lnx+3x)/cos²x+(2tgx-sinx)(1+3x)/x
b) ((6-7ˣlnx)*3eˣ-3eˣ(6x-7ˣ))/9e²ˣ
2)y=x²-5x; y⁾=2x-5
3) a)y⁾=(2-cosx)(lnx+3x)/cos²x+(2tgx-sinx)(1+3x)/x
b) ((6-7ˣlnx)*3eˣ-3eˣ(6x-7ˣ))/9e²ˣ
Автор ответа:
0
Решение на рисунках.
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: agashka19
Предмет: Биология,
автор: kitik79
Предмет: Алгебра,
автор: maksim29karasik
Предмет: Математика,
автор: Mikelson
Предмет: Математика,
автор: tyaroslava1